Effect of intensive versus standard blood pressure control on cerebral blood flow in SPRINT: Neuroimaging / evaluating treatments. (7th December 2020) - Dolui, Sudipto; Detre, John A.; Cho, Monique E.; Haley, William E.; Launer, Lenore J.; Punzi, Henry A.; Rastogi, Anjay; Still, Carolyn H.; Weiner, Daniel E.; Wright, Jackson; Williamson, Jeff D.; Wright, Clinton B.; et al.
Abstract: Background: Hypertension is a major risk factor for cardiovascular and cerebrovascular disease including stroke, small vessel disease, and dementia. The Systolic blood PRessure INTervention (SPRINT) randomized trial prospectively evaluated the effects of intensive systolic blood pressure (SBP) control (target SBP<120mmHg) versus standard control (SBP<140mmHg) on cardiovascular outcomes in individuals without baseline diabetes or stroke, and included cerebral blood flow (CBF) measurements. Previous studies with much smaller sample sizes and shorter duration suggested stable CBF in response to intensive treatment (SBP<125mmHg) [1], but long term effects are unknown. We evaluated the long‐term effects of intensive blood pressure treatment on CBF. Method: Whole brain CBF was measured at 3T using pseudocontinuous arterial spin labeled (ASL) perfusion MRI at baseline and after 3.9±0.3 years. Total white matter lesion (WML) load was measured from Fluid Attenuated Inversion Recovery T2 MRI. Data from 324 subjects with adequate ASL scan quality acquired from 6 sites were included. Result: Demographics and scanner specific CBF values are provided in Table 1. The intensive treatment group was older (p=0.01), but was otherwise similar to the standard group at baseline. There was a significant effect on the longitudinal CBF change (p=0.006) of the intensive treatment (5.7% increase) compared to the standard treatment (4.0% decrease, Fig 1). Secondary analysis showed a significant increase in age‐adjusted fractional CBF for the intensive treatment group (p<0.001) with no change (p=0.24) in the standard treatment group. Change in CBF was not associated with change in WML. Conclusion: Sustained intensive antihypertensive treatment does not reduce whole brain CBF, in fact it showed an increase in whole brain CBF relative to standard therapy. While improved CBF might contribute to the reduced WML progression observed in the intensive‐therapy group versus standard therapy in SPRINT[2], we did not observe a direct correlation between CBF changes and WML changes. References: (1) Croall et al. JAMA‐Neurol, 2018; (2) Nasrallah et al., JAMA‐Neurol, 2019.